2021
DOI: 10.1177/13623613211041006
|View full text |Cite
|
Sign up to set email alerts
|

If you want to develop an effective autism training, ask autistic students to help you

Abstract: Autistic university students face stigma. Online trainings have been used to improve explicit autism stigma (social distance) and knowledge among university students in different countries. However, autistic university students have not typically been involved in developing such trainings. We developed two autism trainings: a participatory training (developed in collaboration with autistic university students) and a non-participatory training. We evaluated these trainings with undergraduate students in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 71 publications
1
40
1
Order By: Relevance
“…An emerging body of literature has shown that interventions combining education and contact can improve the knowledge and attitudes of non‐autistic individuals towards autistic individuals, but findings are inconsistent regarding their effectiveness in changing behavioral intentions (Dachez & Ndobo, 2018; Morris et al, 2020; Ranson & Byrne, 2014; Staniland & Byrne, 2013). Online training programmes have also shown potential to increase understanding and acceptance of autistic people, although recent studies have reported conflicting results on whether such training is more effective at reducing explicit biases or implicit biases (Gillespie‐Lynch et al, 2021; Jones, DeBrabander, & Sasson, 2021). Continued efforts in evaluating and improving such interventions are encouraged so that onus is not placed solely on the autistic community to advocate for them, although it is crucial that these interventions also involve the input of autistic voices.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging body of literature has shown that interventions combining education and contact can improve the knowledge and attitudes of non‐autistic individuals towards autistic individuals, but findings are inconsistent regarding their effectiveness in changing behavioral intentions (Dachez & Ndobo, 2018; Morris et al, 2020; Ranson & Byrne, 2014; Staniland & Byrne, 2013). Online training programmes have also shown potential to increase understanding and acceptance of autistic people, although recent studies have reported conflicting results on whether such training is more effective at reducing explicit biases or implicit biases (Gillespie‐Lynch et al, 2021; Jones, DeBrabander, & Sasson, 2021). Continued efforts in evaluating and improving such interventions are encouraged so that onus is not placed solely on the autistic community to advocate for them, although it is crucial that these interventions also involve the input of autistic voices.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that at least some principles of the neurodiversity movement are not well-aligned with current social norms in South Korea. Therefore, creative work is needed to adapt existing autism trainings, which often emphasize the principles of the neurodiversity movement (e.g., Gillespie-Lynch et al, 2021a ; Jones et al, 2021 ), for South Korean contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Autism knowledge was measured using PAK-M, an instrument adapted from the Autism Awareness Survey (Stone, 1987 ) through collaboration with autistic students (Gillespie-Lynch et al, 2021a ). Participants responded to 29 statements (e.g., “Autistic people show affection”) scored on a 5-point Likert scale, and higher mean scores represented more accurate autism knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some individuals with ASD who received behavioral interventions may not agree with treatment targets (e.g., stereotypy reduction; Kapp et al, 2019) or how the treatment was developed, often without input from the person receiving treatment (Gillespie-Lynch et al, 2021). We interpret these criticisms as reflecting upon instances of poor administration and construction of behavioral interventions, both of which do not align with Wolf's definition of social validity.…”
Section: Example Of How Providers Can Engage With the Neurodiversity ...mentioning
confidence: 98%